Love and loss in wartime: An unpublished narrative by Pamela Frankau (1908–67). Issue 4 (2nd October 2018) - Gonda, Caroline
ABSTRACT: This article discusses an unpublished book by the popular and prolific novelist Pamela Frankau (1908–67), which was rejected by her publishers in 1946 as "almost too personal for publication, " and which for many years was believed lost. The work is addressed to Frankau's dead lover, Marjorie Vernon Whitefoord (1907–44), a fellow officer in the women's Auxiliary Territorial Service, and takes the form of a letter to Vernon. The article examines what Frankau's unpublished narrative of love and loss in wartime reveals about her life and later novels, and its implications for the official record of her life and writing.